DESIGNING SUPPLEMENTARY GRAMMAR MATERIALS FOR GRADE 10 STUDENTS OF MAN1 BATANG HARI BY USING CARRD - Mujapasa, Hannafirsta Seroja; Saharudin; Mardiah, Radiatan (JELT (Jambi-English Language Teaching), 2024)
The English textbook used by grade 10 students has very little grammar material and the work sheet which aims to support the textbook has many grammar errors. Therefore, researcher sees the need to design supplementary grammar materials in the form of website to support students’ independent learning. This research aims to know the process of designing supplementary grammar materials for grade 10 students of MAN 1 Batang Hari and to know the feasibility of the product based on the media validator, content validator, and students’ assessment. The method used is Research and Development. ADDIE Model was used for the framework. The participants of this research are the grade 10 students of MAN 1 Batang Hari. The data of this research were taken through questionnaires and document analysis. The stage of media development started from analysis phase which consists of need analysis and document analysis, then designing the product according to the results of analysis phase, developing the product step-by-step, and implementing the learning website a class of students. The learning website had been validated by validators and the result showed that content validator scored 3.8 content-wise and 4 usability wise. Then, the media validator scored 4.2 appearance-wise and 4.5 programming-wise. According to the level category, the content and media validator deemed this product as feasible and valid to be implemented. The students’ assessment scored 4.5 overall, which is categorized as excellent. Key terms: Supplementary Materials, Development of Learning website, Learning website for grammar materials